Intersectoriality perspectives on the daily life of Primary Health Care in Brazil: a theoretical reflection (Research, Society and Development, 2020)
Objective: to reflect on the perspectives of intersectoriality in the daily routine of Primary Health Care in Brazil. Method: it is a theoretical reflection based on a bibliographic research for theoretical foundation. The study triggered the question: What are the perspectives of intersectoral practices carried out in Primary Health Care services? Results: The reflection was organized into two sections: (1) The expanded concept of health and the promotion of care in the intersectoral dimension. Emphasizes intersectoriality as important in fostering the production of care and expanding the local reality by integrating knowledge, sectors, actors, as they go beyond the performance of the health sector. (2) Health Work Texts in Primary Care with intersectoral articulation. It points out the challenges of producing health in the daily life of services by demanding constant changes in the work process, such as the creation of collectives and partnerships of different social actors, which imposes a logic of work organization to overcome exclusion and inequities in health. Conclusion: intersectorality has been seen as favoring health policies aimed at changing care models, as it represents the overcoming of policy fragmentation, in addition to being a tool for collaborating care and / or management practices.